EKSPRESI Hsa-miR-22-3p PADA URIN PASIEN BENIGN PROSTATE HYPERPLASIA (BPH) SEBAGAI BIOMARKER NON INVASIF - Angga Dwi Prasetyo (BERITA BIOLOGI, 2021)
Benign Prostate Hyperplasia (BPH) is one of prostate diseases with highest prevalence rates men in the world. Benign Prostate Hyperplasia are caused by many factors, such as disorders of androgen receptors, mutations genes, age, epigenetics and environment. Detection BPH in the form of Prostate Specific Antigen (PSA), Transurethral Resection Of Prostate (TURP) and Digital Rectal Examination (DRE) which is invasive in the patient. MicroRNAs in urine eksosomes can be used to detect BPH with non-invasive to patients. This study aims to determine the potential expression of Hsa-miR-22-3p in eksosomal urine samples of BPH as a non-invasive biomarker. This was an observational cross sectional analytic study. Urine samples were obtained from dr. Sardjito Yogyakarta and dr. Soeradji Tirtonegoro hospital. Furthermore, eksosomes isolation, RNA isolation, cDNA synthesis and quantification with qRT-PCR. Based on the results, it is known that Hsa-miR-22-3p decreased expression as much as 29.54 times in BPH, there were significant differences between samples of BPH and normal samples (P = 0.001). Thus Hsa-miR-22-3p has potential as a biomarker in Benign Prostate Hyperplasia.